Evaluation of tabular leg structure of mobile offshore production unit (MOPU) life extension using condition assessment method / Emi Hafizzul Jamaluddin … [et al.] - Jamaluddin, Emi Hafizzul; Razak, Azli Abd; Adenan, Mohd Shahriman; Mohamad, Mohd Faizal (Universiti Teknologi MARA, 2021)
A Mobile Offshore Production Unit (MOPU) is any type of portable structure that can be reused when procuring oil and gas from the seabed. There are few reasons why MOPU is chosen over the conventional fixed offshore platforms, mainly due to its ability to be installed and relocated in a short period, low installation, and abandonment cost, and providing adequate time to evaluate new reservoirs properly. In certain circumstances, MOPU may be required to remain at the same location for a more extended period beyond its designed life. This paper explains the method of life extension (LE) assessment to extend the useful life of the MOPU. A MOPU with a three-legged jack-up rig in cruciform shape designed and constructed based on the American Bureau of Shipping (ABS) Classification requirement with a design life of 5 years, which currently in laid-up mode after 14 years in operation. The legs will be the focus of the condition assessment for the LE of the MOPU. The MOPU was constructed with 3 tabular legs with each 92200 mm length, 3500 mm diameter, and 55 mm thickness operate under tensile and shear stress, standing with simply supported at the one-end with hull hanged at the tabular using jacking-pin at the equal elevation of 77,600 mm. The method of assessment used is Non-destructive Tests (NDT). No severe defects or cracks were recorded at the identified stress concentration points. All NDT measurements were found within the acceptable ranges with no recorded anomalies.